Copper(i)-catalyzed benzylation of triazolopyridine through direct C–H functionalization. Issue 32 (30th July 2019) - Reddy Lonka, Madhava; Zhang, Jinquan; Gogula, Thirupathi; Zou, Hongbin
Abstract : Copper-catalyzed benzylation of triazolopyridine with N -tosylhydrazones through cross-coupling of a C(sp 2 )–C(sp 3 ) bond was developed. Abstract : A general and efficient copper-catalyzed benzylation reaction of triazolopyridine with N -tosylhydrazones was developed. This reaction forms a C(sp 2 )–C(sp 3 ) bond through cross-coupling, and represents an exceedingly practical method to afford 3-benzylated triazolopyridines in moderate to good yields. A proposed mechanistic pathway underlying this reaction was outlined. This catalytic transformation should enable broad synthetic applications in functionalization chemistry, allowing the synthesis of new pharmaceutically relevant triazolopyridine derivatives.